Uma proposta didática para o ensino da Trigonometria no Ensino Fundamental - Siqueira, Anderson Rangel Batista (2014)
The purpose of this work is propound, in some way, contribute to Trigonometry’ teaching improvement in elementary school, according to survey conducted with some teachers who work in the 9th year about basic education that happens in public and private schools in Alagoas State state. For this, it was drawn up a classes sequence for these students divided into four parts. The theme was chosen and developed with intention of reducing a great difficulty found by students in a content’s comprehension, and enable a better applicability in problems, mainly because we believe that the understanding by some concepts, you can enable the student to perform arithmetic operations, algebra and geometry to extent that are presented. We propose the teaching Trigonometry through the resolution of problems, in particular the design’s construction that facilitates the subject’s visualization and interpretation coming to your solution, because in this way, we believe that students can develop their own resolutio’s skills.